The Importance of Serum Homocysteine as a Biomarker in Diabetic and Obese COVID-19 Patients: Serum Homocysteine as a Biomarker in COVID-19 - Shawkat Ahmed, Haitham; Noori, Saman Hussein (Cellular and Molecular Biology, 2023)
Homocysteine is a possible risk marker in hematological complications of COVID-19 infection. This study aimed to elucidate the significance of homocysteine as a biomarker for COVID-19 infection, and the relation of homocysteine with COVID-19 severity in obese people and diabetic patients. The study groups were 1- COVID-19 patients + Diabetic + Obese (CDO), 2- COVID-19 patients + Diabetic (CD), 3- COVID-19 patients + Obese (CO), 4- Healthy Group (HG). Serum levels of homocysteine, IL-6, D-dimer, vitamin B12, and folate were measured by a fully automated biochemistry device Cobas 6000 analyzer series. The mean serum concentration of homocysteine in the COD, CD, CO and H groups were 32.0114, 23.604, 19.4154, and 9.3206 umol/l respectively. The mean concentration of homocysteine levels between every two groups was statistically significant differences (P<0.05) except for the CD and the CO group (P=0.957). In the CDO group, the males have higher mean concentrations than females (P<0.05). The means of homocysteine concentrations in the CDO group among different age groups were different (P <0.001). The serum homocysteine level in the CDO group has a strong positive correlation (R=0.748) with D-dimer and a strong negative correlation (R= - 0.788) with serum folate, while its correlation with serum vitamin B12 is moderate negative (-0.499) and its correlation with serum IL-6 is weakly positive (R=0.376). The AUC value for homocysteine in predicting COVID-19 in the CDO group was 0.843, while 0.714 for the CD group, and 0.728 for the CO group. The serum homocysteine concentration test for all study groups was compared to the serum IL-6 test and the sensitivity was equal to 95% and its specificity was 67.5%. Serum homocysteine has potential predictive power in COVID-19 patients, and the severity of COVID-19 infection and the type of comorbidity is associated with higher sensitivity and specificity of homocysteine serological tests.